The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2355/isijinternational.isijint-2019-321
|View full text |Cite
|
Sign up to set email alerts
|

Supergravity-Induced Separation of Oxide and Nitride Inclusions from Inconel 718 Superalloy Melt

Abstract: Herein, a method of supergravity-enhanced separation was used to remove oxide and nitride inclusions from Inconel 718 superalloy melt, with elucidating the inclusion removal behavior by varying the gravity coefficients (G) and separation times (t) used for melt treatment. Under supergravity conditions, inclusions concentrated at the sample top and are almost absent at the sample bottom. Moreover, the inclusion number density and average size showed a gradient distribution along the supergravity direction, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The supergravity field can achieve the separation of suspended dross and liquid as an efficient method used to separate components of complex materials based on the differences in the relative movements of the heterogeneous phases in the supergravity field. 16,17 The supergravity separation technology has also been successfully applied to purify metals such as steel, Al, and Sn. [18][19][20] Some researchers studied the influence of the supergravity field on zinc slag and inclusions in different materials and showed that the supergravity field could realise the separation between different phases.…”
Section: Introductionmentioning
confidence: 99%
“…The supergravity field can achieve the separation of suspended dross and liquid as an efficient method used to separate components of complex materials based on the differences in the relative movements of the heterogeneous phases in the supergravity field. 16,17 The supergravity separation technology has also been successfully applied to purify metals such as steel, Al, and Sn. [18][19][20] Some researchers studied the influence of the supergravity field on zinc slag and inclusions in different materials and showed that the supergravity field could realise the separation between different phases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on the different density of metal melt and inclusion, Meng et al 18) achieved the purification of scrap Al-Mg alloys by supergravity, leading to a concentration of nonmetallic inclusions and Fe-rich impurities at the bottom of the alloy and an increase in enrichment proportional to the gravity coefficient. Shi et al 19) employed supergravity to separate Al 2 O 3 and TiN inclusions from 718 superalloy, which induced the migration of most inclusions to the top of the sample and a decrease in total O and N contents from 34.4 ppm to 8.7 ppm and 133.4 ppm to 34.1 ppm, respectively. Given the successful applications of supergravity in metal purification, it is considered feasible to use supergravity to remove oxide impurities from waste NdFeB magnets.…”
Section: Introductionmentioning
confidence: 99%
“…34,35) However, the control of strict pouring temperature is difficult. Shi et al 36) have investigated the effect of supergravity-induced separation on the removal of oxide and nitride inclusions from IN718 alloy melt. The removal behavior of inclusions is dependent on the gravity coefficients (G) and separation times (t).…”
Section: Introductionmentioning
confidence: 99%